Analysis of the Spatial Distribution of Seawater Intrusion Using a Hydrogeochemical Approach: A Study of the Coastal Geology of Kebumen Regency, Indonesia - Faidatuz Zahroh; Muhammad Asyroful Mujib; Sri Astutik; Bejo Apriyanto; Era Iswara Pangastuti (Geosfera Indonesia, 2024)
This study examines seawater intrusion in the southern part of Kebumen District, focusing on the impact of various geological formations on groundwater salinity. Groundwater samples were systematically collected from 11 locations representing alluvial, volcanic, coastal sediment, and karst geological conditions. The samples were analyzed for major ions, including calcium (Ca²⁺), magnesium (Mg²⁺), chloride (Cl-), and bicarbonate (HCO₃-), as well as Total Dissolved Solids (TDS). Ion ratios such as Mg²⁺/Ca²⁺, Cl⁻/HCO₃⁻, and Mg²⁺/(Mg²⁺+Ca²⁺), along with the Fraction of Seawater (fsea), were calculated to assess the extent of seawater intrusion. The study employed the Gibbs diagram method to identify the primary processes controlling groundwater chemistry, revealing that water-rock interactions are dominant in most samples, particularly in those affected by seawater intrusion. The results indicate significant seawater intrusion in alluvial and karst regions, especially at sampling points TP 2, TP 4, and TP 10, while volcanic and coastal sediment areas show minimal intrusion. These findings underscore the critical influence of geological conditions on seawater intrusion and highlight the need for targeted groundwater management strategies. Further research focusing on long-term monitoring is recommended to better understand and mitigate the impacts of seawater intrusion in this region.